Serum potassium concentration and its association with hypertension among Ghanaian migrants and non-migrants: The RODAM study. (February 2022) - Ndong, Amie K.; van der Linden, Eva L.; Beune, Erik J.A.J.; Meeks, Karlijn A.C.; Danquah, Ina; Bahendeka, Silver; Klipstein-Grobusch, Kerstin; Schulze, Matthias B.; Addo, Juliet; van den Born, Bert-Jan H.; Agyemang, Charles
Abstract: Background and aims: Low serum potassium concentration is associated with hypertension, but whether the same association can be found in African origin populations, is unknown. We assessed serum potassium concentration, and its association with hypertension among Ghanaians living in different geographical locations. Methods: Baseline data of 962 rural, 1420 urban, and 2947 migrant Ghanaians from the Research on Obesity and Diabetes among African Migrants study were analysed. Mean serum potassium concentration was compared between the groups, and the association between serum potassium and hypertension was assessed using multivariate regression analyses. Results: Mean serum potassium concentration was higher in rural Ghana (4.28, 95% confidence interval 4.25–4.32 mmol/L) than in Ghanaians living in Amsterdam (3.90, 3.88–3.92 mmol/L) and London (4.11, 4.07–4.14 mmol/L), but lower than in Ghanaians living in urban Ghana (4.38, 4.34–4.42 mmol/L) and Berlin (4.57, 4.51–4.62 mmol/L) in both sexes. In the age-adjusted analyses, serum potassium was associated with hypertension in urban- (odds ratio 0.44, 0.23–0.82), London- (0.34, 0.17–0.64) and Amsterdam-Ghanaian males (0.41, 0.20–0.86), and in rural- (0.49, 0.28–0.84), London- (0.29, 0.17–0.49) and Amsterdam-Ghanaian females (0.33, 0.17–0.64). However, after adjustment for demographic, lifestyle, and health factors, serum potassium was associated with hypertension in Amsterdam-Ghanaian males only (0.12, 0.02–0.59). Conclusions: This study shows differences in mean serum potassium among Ghanaian populations living in different locations in Europe and Ghana, and different associations with hypertension between sites. Further research should focus on elucidating the mechanism underlying potassium handling and blood pressure regulation in African populations, in order to mitigate the burden of hypertension among these populations. Graphical abstract: Image 1 Highlights: Serum potassium concentration differs between Ghanaians in Ghana and Europe. Lower serum potassium is associated with higher odds of hypertension. This association varies between Ghanaians in different geographical locations. This association is largely explained by demographic, lifestyle and health factors.